Programming 3D applications in HTML5 and WebGL : 3D animation and visualization for web pages - Parisi, Tony (O'Reilly Media, 2014)
"Learn how to create high-performance, visually stunning 3D applications for the Web hands-on, using HTML5 and WebGL. With this interactive video course, you'll learn by using the tools, frameworks, and libraries for building 3D models and animations, mind-blowing visual effects, and advanced user interaction in both desktop and mobile browsers. Lead by Tony Parisi, a pioneer of 3D standards for the Web, this course provides a thorough grounding in theory and practice for designing everything from a simple 3D product viewer to immersive games and interactive training systems. This course is divided into two parts"--Resource description page.